Brand emotional connection and loyalty - Loureiro, S.M.C.; Kaufmann, H. R.; Vrontis, D. (Journal of Brand Management, 2012)
This study, for the first time, aims to integrate brand attachment as an antecedent of brand love and both, affective commitment and brand trust as mediators between brand love and loyalty. It is also the first time that differences between male and female consumers perceptions on this topic have been compared in literature. On the basis of previous research, a model was developed and validated using consumers who bought one of three car brands: Toyota, Ford and Renault. Living in three regions of Portugal, the sample consisted of consumers who bought a new car 2 years before the research and had declared being satisfied with the purchase. The model is tested in the context of a non-hedonic product, differing from the common perspective that focuses on hedonic products. Hypotheses were tested by employing multi-group structural equation modeling. Findings suggest that brand attachment is positively related to brand love. Brand love reinforces the trust, interest in continuing a relationship and faith in the future of the brand. Women exhibited trust and placed more importance on dyadic relationships than did men. Men, however, desired to identify socially with the brand.